The Fraud, Futility and Hypocrisy of Charity for the Blind - Perry, J.; Davis, J.
1923 1923 1920s 1 page The Fraud, Futility and Hypocrisy of Charity for the Blind. An exposure and appeal by the London District Council of the National League of the Blind of Great Britain and Ireland. Fellow Citizens, The National League of the Blind is the blind workers Trade Union, and for almost thirty years has been actively engaged improving the conditions of the Blind and exposing the fraud, futility and hypocrisy of the Charity System. Still the public generally believe that the blind are well cared for by the many Charity Associations which issue pathetic appeals and collect finance ostensibly for the welfare of those bereft of sight. It is however not necessary to be very observant to prove the [ ]acy of such belief, for in almost every main street, the Blind are to be seen exhibiting their affliction as a means of obtaining a precarious existence. Approximately two years ago, three officials of Blind institutions were sent to prison, one for three years and the other two for lesser terms, for embezzling the funds subscribed by the sympathetic public. In a pamphlet entitled The Social and Industrial Conditions of the Blind, the following statement appears; Philanthropic people are frequently the dupes of interested officialism. Mr. B. Purse is the author of the pamphlet and he is at present an official of the National Institute for the Blind Great Portland St. On May 5th, Councillor H. Roberts drew the attention of the L.C.C. to the fact that the Blind Ballot of the National Institute for the Blind, brought in £87,000 and that £64,000 had gone in salaries, profits, expenses and commissions etc; leaving £23,000 for the Institute. The Greater London Fund for the Blind collects annually, approximately £40,000 but approximately 50% is absorbed in salaries and collecting expenses etc. In replying to Mr. Blake at the L.C.C. meeting June 30th, the Chairman of the committee on the Welfare of the Blind stated that at March 31st, there were 4,485 Blind persons residing in the County of London, and if the total income of the Charities for the Blind registered by the Council for the year ending March 31st, 1923. £571,743 was equally divided, it would be sufficient to provide an annual income of £127. 9s. 7d. for each blind person. Still hundreds of of our Blind are incarcerated in London Workhouses, hundreds more are condemned to beggary, and those who are employed are compelled to work piece work. For the past 18 months the blind workers of London have been appealing to their Charity Managers to abolish piece work and give them a living wage, on three different occasions a hall has been rented and the Institutions have been invited to send representatives to discuss the subject with blind workers; but only two Institutions acknowledged the communications to them, and all of them ignored the arranged conferences. These self advertised tender hearted Charity officials draw exorbitant salaries, and all the sighted persons employed in a Blind institution enjoy decent wages and they do not work piece work. It is only the blind worker that is compelled to work piece work and if possible earn all he gets. The London District Council of the National League of the Blind therefore respectfully request you to send a note or resolution to the L.C.C. calling upon that body to exercise its powers under the Blind Persons Act 1920. and abolish the Charity cadging nuisance with its abuses, and degradation of the Blind. Mr. J. DAVIS, Chairman. Mr. J. PERRY, Secretary. Lovell, Printer, (T.U) 61, Kentish Town Road, N.W.1. 292/841.4/1/2